From Philosophy to Design: Philosophy of Ethno-Design in the Education System of Kazakhstan - Ezieva Nehir Езиева Нехир (Рroblems of engineering and professional education, 2022)
The philosophy of ethnodesign is a modern system of education as a discipline. At the end of the XX at the beginning of the XXI centuries. the education system in Kazakhstan has changed. New courses appeared in the education system, the content of the courses was changed. The uncertainty of the theory and philosophy of designing, which is embedded in the education system, made it possible to write this arthiko. The discipline "Philosophy of Design" will help the teacher to comprehensively analyze his abilities in the near future.